2008
DOI: 10.3727/096368908786991579
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Proline-Rich Polypeptide Enhances Bone Marrow Colony-Forming Cell Proliferation and Stromal Progenitor Cell Differentiation

Abstract: The AGAPEPAEPAQPGVY proline-rich peptide (PRP-1) was isolated from neurosecretory granules of the bovine neurohypophysis; it is produced by N. supraopticus and N. paraventricularis. It has been shown that PRP-1 has many potentially beneficial biological effects, including immunoregulatory, hematopoietic, antimicrobial, and antineurodegenerative properties. Here we showed that PRP increased colony-forming cell (CFC) proliferation in rat bone marrow (BM) cells in vivo. In PRP-treated rat BM, the CFU number at da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The regulating effect of PRP on myelo-and granulocytopoiesis as well as its immunostimulating, antineurodegenerative and other properties were demonstrated in previous studies [21]. Recent findings [22] demonstrated a two to threefold increase of CFC numbers in methylcellulose cultures of rat bone marrow obtained on Day 4 after PRP 10 lg administration. PRP addition to cultures of bone marrow obtained from control animals and from rats which had been administered PRP did not result in any additional increase of colonies.…”
Section: Discussionmentioning
confidence: 63%
“…The regulating effect of PRP on myelo-and granulocytopoiesis as well as its immunostimulating, antineurodegenerative and other properties were demonstrated in previous studies [21]. Recent findings [22] demonstrated a two to threefold increase of CFC numbers in methylcellulose cultures of rat bone marrow obtained on Day 4 after PRP 10 lg administration. PRP addition to cultures of bone marrow obtained from control animals and from rats which had been administered PRP did not result in any additional increase of colonies.…”
Section: Discussionmentioning
confidence: 63%
“…Recently we found that PRP-1 increased colony-forming cell (CFC) proliferation in rat BM cells in vivo, whereas the related peptide [arg 8 ] vasopressin did not reveal CFC proliferation. Moreover, PRP-1 increased the appearance of CD14 positive cells upon 3-4 day incubation with both adult and fetal BM stromal cells [15]. These results suggest a previously indescribed role for the hypothalamic peptide within neurosecretory hypothalamus-bone marrow humoral axis, since PRP enhances BM colony forming cell proliferation and stromal cell differentiation.…”
Section: Introductionmentioning
confidence: 58%
“…The related peptide [arg 8 ] vasopressin did not reveal CFC proliferation. Interesting, that PRP-1 increased the appearance of CD14 positive cells upon 3-4 day incubation with both adult and fetal human BM stromal cells [15]. One possible mechanism of such action would be influence of PRP-1 on BM cells apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…PRP-1 is derived from its precursor, neurophysin-vasopressin-associated glycoprotein precursor (20). In addition, large quantities of PRP-1 were detected in bone marrow granulocytes (21). The antimicrobial, antitumorigenic and antineurodegenerative properties for this immunomodulatory cytokine were previously reported (22) and the quantification of hypothalamic PRP-1 in the blood was recently documented (23).…”
Section: Neuropeptides Involved In Epigenetic Control Of Cancermentioning
confidence: 90%